Aplicação de técnica de geoprocessamento em áreas degradadas de mata ciliar e sua correlação com qualidade da água numa subbacia hidrográfica - Belluta, Ivalde [UNESP]; Neves, Renato de Casio Ferreira [UNESP]; Zampieri, Fábio Eduardo de Souza [UNESP]; da Silva, Ramon Felipe Bicudo [UNESP]; Sartori, Anderson Antonio da Conceição [UNESP]; Zimback, Célia Regina Lopes [UNESP] (My University, 2011)
Studying the physical environment of a watershed is the basic condition for a successful planning of the riparian forest preservation, and for water production and conservation. The aims of the present study were to analyze and quantify the spatial and temporal evolution (1984 and 2010) using Landsat-5 satellite images of Cintra Stream sub-watershed, Botucatu, São Paulo State, Brazil, processed by the software IDRISI Andes, as well as to analyze the water quality through the parameters pH, EC, DO and BOD5 at 4 different sites in the years 1999, 2008 and 2009. Considering the 1076.48ha area of the sub-watershed, the pasture class of 1984 was reduced by 25.55% in 2010, resulting in an increase in the remaining classes. The most important class was native forest and reforestation since it had an increase of 5.08%, which indicates recovery of the riparian forest. Degraded areas were identified close to the inferior limit of the sub-watershed (P3 and P4), as well as local contamination (P1 and P2) with worsening of the water quality in the remaining sites in the periods 2008 and 2009. Recovery and management of the ecological succession of degraded areas and water quality monitoring at 1 and 2 sites will be necessary to reestablish the natural condition of the area studied.

O estudo do meio físico de uma bacia hidrográfica é condição básica para o planejamento bem sucedido da preservação da mata ciliar e conservação e produção de água. Os objetivos do presente trabalho foram analisar e quantificar a evolução espacial e temporal (1984 e 2010) através de imagens de satélite Landsat-5, da sub-bacia do córrego do Cintra, Botucatu SP, processadas pelo sistema computacional IDRISI Andes, e analisar a qualidade da água pelos parâmetros pH, CE, OD e a DBO5 em 4 pontos distintos nos anos de 1999, 2008 e 2009. Considerando a área de 1076,48ha da sub-bacia, observou-se que a classe pastagem em 1984 foi reduzida em 25,55% em 2010 resultando no aumento das demais classes. A mais importante foi a classe mata nativa e reflorestamento, pois aumentou 5,08%, o que demonstra recuperação da mata ciliar. Foram identificadas áreas degradadas situadas no limite inferior da sub-bacia (P3 e P4) e contaminação pontual (P1 e P2) com piora na qualidade da água nos demais pontos nos períodos de 2008 e 2009. Restauração e manejo de sucessão ecológica nas áreas degradadas e o monitoramento da qualidade da água nos pontos 1 e 2 serão necessários para restabelecer a condição natural na área de estudo.
Geoprocessing technique used in degraded areas of riparian forest and their correlation to the water quality in a watershed
Keywords: Cintra stream; Georeferencing; Idrisi andes; Physicochemical parameters; Riparian forest; data processing; environmental degradation; environmental monitoring; Landsat; physicochemical property; riparian forest; satellite imagery; spatiotemporal analysis; stream; temporal evolution; water pollution; water quality; watershed; Botucatu; Brazil; Sao Paulo [Brazil]